"Where did I park my car?" How do older adults cope with a diagnosis of mild cognitive impairment - McKinlay AR; Leathem JM; Merrick PL (My University)
Background: This presentation will background a New Zealand based research study to be conducted this year focusing on how people cope with and adjust to a diagnosis of mild cognitive impairment (MCI). This area of research is important because as a person reaches older age, their chances of developing a certain set of age related illnesses, such as dementia and cognitive impairment increases (Larson, 2010; Coulson et al., 2005; Hughes & Heycox, 2010). At the same time, the number of adults aged 65 and over is set to increase at levels unseen in Western Society to date in coming years. By 2050, the world's population of older adults is estimated to reach over 22% in its entirety, which roughly equates to a staggering 1 and a quarter billion people (Lloyd-Sherlock, 2010). Adjusting to and coping with a diagnosis of cognitive impairment can be difficult and is comparable to receiving a diagnosis of other chronic diseases (Preston, Marshall & Bucks, 2007). Some report depression, anxiety and other psychological reactions following their dementia diagnosis (Carpenter et al., 2008). Current literature to date is divided on how people react psychologically to knowing that they have a progressive cognitive impairment, and much of the research has overlooked the issue of MCI and the associated reactions to this diagnosis.
Keywords: mild cognitive impairment; older adults; coping